Against Self-Interest: Trollope and Realism - Small, H (Oxford University Press, 2012)
Extract: IT IS A STRIKING TRAIT of many Trollope protagonists, Stephen Wall observes in his fine study Trollope and Character, that they act ‘against self-interest’. They are capable of discerning what it would be best for them to do, in the sense that it would tend to promote their worldly advantage or their personal happiness, but how they behave is not in accordance with that judgement. Their acting so disadvantageously to themselves, in ways that are not explained by alternative calculations or even clear emotional imperatives, has, moreover, a vital bearing on the reader's apprehension of their ‘reality’. ‘Casualties of their own wills’ as they are, in Wall's deft phrase (p. 57), their propensity for self-sabotage confirms Trollope's ‘intense respect for the[ir] experience’: they ‘liv[e] in his mind’ in a way that ‘seems to preclude any thought of … ethical or rhetorical exploitation by the novelist’ (pp. 57, 61). To argue so is, up to a point, to say something familiarly within the traditions of description for classic realism. Characters impress us with their reality in so far as they establish their singularity, escaping or pre-empting the characterological straitjackets of genre, mode, stereotype, and moral formula. In Trollope's most persuasive endeavours at rendering ‘the authenticity of presence’ (p. 76) there is a touch of that quality Auerbach admired in Flaubert: a sense of something ‘unget-at-able’ in an individual nature, troubling the character him or herself and reinforced by the writer's more or less resigned awareness that literary representation cannot (should not?) hope to do better than the character themselves in this respect, and must accept the ‘hopelessly inexplicable’ aspects of motive (p. 76). This is, Wall suggests, largely what we mean by respect for the autonomy of others: accepting the impossibility of subduing them, in art as …